The house of Kwee Sik Poo; An Indonesian-Chinese merchant from Pasuruan - Sien, Kwee Hong (Wacana, Journal of the Humanities of Indonesia, 2017)
The Kwee family is an old Indonesian-Chinese family from Pasuruan, in East Java, and one of a few merchant families of either Chinese or Arab ethnic origin which led successful lives in this small town in the nineteenth century. From their Chinese ancestral village, Liu Chuan in Fujian province, China, a Kwee ancestor travelled to Southeast Asia and settled in Pasuruan, probably in the eighteen century. As with many families who held important positions in the ethnic Chinese community, it also owned large homes, mostly in a mixed architectural style, called "eclecticism" and later in what was known as "the Indies-empire style". The early family history is still clouded in mystery, as not much concrete information has survived. Its descendants worked hard and prospered and dealt among economic undertakings such as sugar production, opium sales, buying and selling of property and land as well as running pawnshops.